Surface contour error model of five-axis machining considering multifactor coupling effects. (December 2021) - Ge, Shuyi; Wang, Liping; Yu, Guang
During five-axis flank milling procedure, the static deflection of workpiece and cutter creates surface errors that lead to defects in projects with strict requirements, especially in thin-walled parts industry. Focusing on the mentioned issues, the surface contour error is predicted in this paper considering the coupling between the deflection and cutting force. First, an efficient calculation method of the cutting force is presented in five-axis flank milling. This method accounts for the impact of cutter runout on cutter/workpiece engagement (CWE) and the instantaneous undeformed chip thickness (IUCT). Then, a cutter is modelled as a cantilever structure and thus an analytical solution for the deflection of the end mill can be obtained. Next, the flexible cutting force is distributed on a finite element (FE) model of workpiece, while the workpiece stiffness keeps varying with the material removal. Subsequently, a flexible iterative calculation method for achieving deflection prediction is established. Finally, the prediction model is proven by machining tests of an S-shaped specimen in which predicted values of the surface error match with the experimental results.